STUDI TERHADAP KOMPETENSI KEPALA SEKOLAH PADA SDN NUSAWUNGU 03 DAN SDN NUSAWUNGU 05 - Asihandriyani (Pusat Studi Pendidikan dan Kreativitas Guru, 2018)
The purpose of this study is to know how to describe theimplementation of the principal’s leadership in implementing its competence toimprove the quality of education, to know how the achievement of school canbe achieved, to know the role of headmaster’s competence to face obstacles incarrying out its duties. The approach in this research is qualitative naturalisticapproach. In this approach will be more concerned with the process than theresults. Objects in this study is Principal Competence in Improving EducationQuality. Technique of collecting data is done by interview, observation anddocumentation. The result of this research concludes that 1) Principal of SDNNusawungu 03 and SD Negeri Nusawungu 05 sub district Nusawungu CilacapRegency in carrying out its leadership have implemented its Competence thatis in Personality Competence, Social Competence, Managerial Competence,Competence Supervisi and Entrepreneurship Competence well. In addition, thePrincipal has integrity, determination, spirit, competence/ability in self-behaveand establish relationships with existing stakeholders. 2) School achievement atSD Negeri Nusawungu 03 and SD Negeri Nusawungu 05 District NusawunguCilacap Regency in both academic and non academic at sub-district level is goodenough. 3) In overcoming various obstacles that exist, Principal in applyingleadership competence in improving Quality of Education, sourced frominternal aspect of school principal and external aspect of school principal.